Althusserian Theory: From Scientific Truth to Institutional History - Philip Goldstein (Studies in 20th & 21st Century Literature, 1994)
Scholars have emphasized the scientific and the rationalist features of Althusser's work, but few have noted its post-structuralist aspects, especially its Foucauldian accounts of discourse and power. In the early Pour Marx, Althusser divides ideological practices from objective science and theoretical norms from empirical facts; however, in several later essays Althusser repudiates his earlier faith in theory's normative force as well as his broad distinction between science and ideology. He argues that every discipline establishes its own relationship between its ideological history and its formal, scientific ideals. This argument, together with Althusser's earlier rejection of totalizing approaches, establishes important parallels with Foucault's archaeological studies. The literary theory of Tony Bennett, who develops a Foucauldian critique of traditional and Marxist aesthetics, illuminates the rich implications of these parallels for cultural analyses.
Keywords: Althusser; post-structuralist; post-structuralism; Foucauldian; discourse; power; Pour Marz; ideology; science; archaeology; cultural analysis; culture; Marxist philosophy